2021
DOI: 10.1177/09603271211026729
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol hinders the progression of hepatic fibrosis via targeting autotaxin and thioredoxin in thioacetamide-induced liver fibrosis in rat

Abstract: Fibrosis is a common outcome of nearly all chronic diseases of liver that results in changes of its functions which requires medical attention. The current research aims to investigate the potential anti-fibrotic efficacy of Carvacrol against thioacetamide (TAA)-induced liver fibrosis in male rats using Ursodeoxycholic acid (UDCA) as a reference anti-fibrotic product. Carvacrol (25 and 50 mg/kg) markedly declined TAA-increased serum liver enzymes; alanine aminotransferase (ALT), aspartate aminotransferase (AST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
6
5
0
Order By: Relevance
“…While serum levels of GGT were significantly increased as compared to the control group. These results were in agreement with Salama et al, 31 El-Gendy et al 37 and Ayoub et al 33 The combined administration of TAA with LF and QD showed a non-significant decrease in serum hepatic enzymes indicating that both may have a protective effect against TAA hepatotoxicity. The downregulating effect of LF and QD against serum-level enzymes was reported by Bahr et al 38 and Afifi et al, 39 respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While serum levels of GGT were significantly increased as compared to the control group. These results were in agreement with Salama et al, 31 El-Gendy et al 37 and Ayoub et al 33 The combined administration of TAA with LF and QD showed a non-significant decrease in serum hepatic enzymes indicating that both may have a protective effect against TAA hepatotoxicity. The downregulating effect of LF and QD against serum-level enzymes was reported by Bahr et al 38 and Afifi et al, 39 respectively.…”
Section: Discussionsupporting
confidence: 91%
“…48 control rats. The same result was obtained by Đurašević et al 32 and El-Gendy et al 37 Furthermore, Abdel-Rahman et al 35 showed that the intraperitoneal injection of TAA (100 mg/kg) for 2 weeks resulted in a substantial increment in hepatic fibrosis markers as TGF-β1, collagen I, connective tissue growth factor (CTGF), focal adhesion kinase (FAK) and α-SMA. LF showed antifibrotic activity as demonstrated by the down-regulation of α-SMA-stained myofibroblast and collagen expression by Masson's trichrome.…”
Section: Discussionsupporting
confidence: 67%
“…42 Recent studies have proven the anti-inflammatory activity of CVL by modulating TNF-α, IL-1β, and NF-κB expression in rat models of diclofenac-induced kidney injury and thioacetamide-induced hepatic fibrosis. 43,44 In the current study, UUO-induction dramatically increased the renal recruitment of inflammatory cells and the pro-inflammatory cytokines TNF-α and IL-1β in the obstructed kidneys. However, we observed a marked decrease in inflammatory cell infiltration and low levels of TNF-α and IL-1β in the obstructed kidneys after CVL administration.…”
Section: Discussionsupporting
confidence: 50%
“…Carvacrol reduced glutathione depletion (GSH), NO, and MDA accumulation in liver tissue. The anti-inflammatory effect of carvacrol was confirmed by decreasing nuclear factor kappa B (NF-κB), IL-1β, and inducible nitric oxide synthase (iNOS) contents (57). Oral administration of carvacrol had a significant protective and antioxidant effect against D-GalN-induced damages by reducing AST, ALT, ALP, and GGT and increasing SOD, CAT, and glutathione peroxidase in the plasma and liver (58).…”
Section: Discussionmentioning
confidence: 98%